Navigating the Future: Strategies of EdTech Companies in Driving Educational Transformation - Adeoye, Moses Adeleke; Otemuyiwa, Bridget Idowu (STKIP Pesisir Selatan, 2024)
The EdTech industry is undergoing a significant transformation due to the rapid advancement of technology and the emergence of innovative companies. This research discourse examines the strategies employed by EdTech companies, such as personalized learning, data analytics, gamification, and AI integration, which are reshaping the educational experience across various levels of learning. The study highlights the impact of these strategies on educational outcomes, accessibility, and engagement among diverse learner populations. However, the research also identifies critical gaps in existing literature, such as the long-term efficacy of EdTech solutions, the digital divide, and ethical considerations surrounding data privacy and security in educational settings. Future research directions can emphasize the need for a multidisciplinary approach, incorporating insights from educational psychology, sociology, and technology studies. This discourse serves as a foundation for scholars, practitioners, and policymakers to navigate the evolving EdTech landscape and leverage technology to benefit all learners